Global Well-Posedness and Convergence Results to a 3D Regularized Boussinesq System in Sobolev Spaces - Ridha Selmi; Shahah Almutairi (Journal of Mathematics)
We consider a regularized periodic three-dimensional Boussinesq system. For a mean free initial temperature, we use the coupling between the velocity and temperature to close the energy estimates independently of time. This allows proving the existence of a global in time unique weak solution. Also, we establish that this solution depends continuously on the initial data. Moreover, we prove that this solution converges to a Leray-Hopf weak solution of the three-dimensional Boussinesq system as the regularizing parameter vanishes.